Arsitektur Moisture Meter dengan Capacitive Sensing dan Serverless IoT Untuk Hidroponik Fertigasi - I Wayan Aditya Suranata; I Gede Humaswara Prathama (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
The current agricultural systems generally uses chemical fertilizers as a growth booster in order to meet the global food needs of 7 billion people and all of their livestock. But unfortunately not all are aware of the great danger behind such an overuse, unmetered application of chemical fertilizers, freely in an open field for the survival of the planet and its population. Thanks to technological advances, especially in the field of instrumentation and communication technology, the problem of increasing efficiency and avoiding such overuse should be minimized properly. In this study, the researchers tried to apply capacitive moisture sensor technology and serverless Internet of Things to the moisture meter instrument in the hydroponic drip fertigation system with roasted husk planting media. Capactive sensor technology has the advantage of corrosion resistance when applied to planting media containing high humidity and low alkalinity. By using a serverless IoT architecture, it is possible to monitor from anywhere via the internet, without involving complicated and expensive infrastructure. Based on the results of the prototype testing, it is known that the instruments built can work properly. The results of monitoring system conditions such as temperature and free heap appear stable. The reading results of the two sensors also run steadily, without fluctuations and variations in the reading that exceed 5%. The process of remote monitoring and data logging to serverless IoT is monitored to be stable with a data recording success rate of 99.8%.